Analysis of Metaphor in Ads From Cognitive Perspective - Xiaqing, Li (Advances in Social Sciences Research Journal, 2017)
Previous researchers at home and abroad mainly drew their attention to studies on eternal forms of ads. Audience’s thinking processes of ads were not systematically explained. In recent years, the analysis of ads from a cognitive perspective is promising. Cognitive analysis of ads is meaningful to explore ad receivers’ transference of their cognition as a result of the realization of promotion. Metaphor focused on cognitive linguistics. Cognitive linguistics is widely used in advertising communication so as to make advertising promotion go on successfully. The analysis of metaphors in ads will show us functions of metaphor in advertising discourse. Cognitive linguists consider metaphor, which is pervasive in our ordinary language, as a important mechanism of cognition and a mode of thinking of human beings on conceptual level. In this thesis the author takes a cognitive method to analyze ads.